2020
DOI: 10.1021/acs.energyfuels.0c03305
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Nanostructure Transitions of Soot with Various Dimethyl Ether Additions in Nonpremixed Ethylene Flames at Different Scales

Abstract: This work experimentally investigated the broad ranges of dimethyl ether (DME) additions (0−100%) to ethylene on soot formation at different scales (combustor diameter) by both optical diagnostic and sampling methods. According to the optical result by a two-color method, the overall temperature and soot concentration increased slightly when DME was added from 0 to 10% but they decreased rapidly with much DME addition from 20 to 100%. Such a synergistic effect was more pronounced in the larger combustor diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This is because the initial introduction of the oxygenated fuels changes the combustion environment from that of a pure diffusion flame to a partially premixed flame. This can have a non-uniform effect on the pyrolysis mechanism [127][128][129] and is known to affect flames with oxygenated fuel blends [130]. The dilution effect will also play a role and it is expected to have a non-linear effect, particularly at low blend strengths (because soot precursors are formed via non-linear reactions).…”
Section: Correlations Of Soot Measurements To Fuel Blend Oxygen/carbo...mentioning
confidence: 99%
“…This is because the initial introduction of the oxygenated fuels changes the combustion environment from that of a pure diffusion flame to a partially premixed flame. This can have a non-uniform effect on the pyrolysis mechanism [127][128][129] and is known to affect flames with oxygenated fuel blends [130]. The dilution effect will also play a role and it is expected to have a non-linear effect, particularly at low blend strengths (because soot precursors are formed via non-linear reactions).…”
Section: Correlations Of Soot Measurements To Fuel Blend Oxygen/carbo...mentioning
confidence: 99%
“…Diverse studies [4,[6][7][8] have shown that the addition of small amounts of DME to methane, ethylene, ethane, and propane flames create a synergetic effect that enhances soot production due to its chemical effects, but further additions radically reduce soot concentration. Despite the important efforts in the literature to scrutinize DME combustion, DME's characteristics as a single fuel in flames have not been deeply studied, especially for laminar configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Various nanostructures have been fabricated for PEC water splitting applications, including nanosheets, nanorods, nanocoral, nanotubes, and nanocrystals. ZnO nanorod arrays have shown great potential in several energy storage applications such as optoelectronics, photonics, solar cells, and sensors . Especially, nanorod arrays have received greater attention in PEC water splitting due to their advantage of highly ordered geometrical structures, which increase the charge transfer efficiency and light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanorod arrays have shown great potential in several energy storage applications such as optoelectronics, photonics, solar cells, and sensors. 10 Especially, nanorod arrays have received greater attention in PEC water splitting due to their advantage of highly ordered geometrical structures, which increase the charge transfer efficiency and light absorption. Numerous methods are being investigated to further improve PEC presentation of metal oxides like structural engineering, use of nanocomposites, and quantum dot sensitization.…”
Section: ■ Introductionmentioning
confidence: 99%